2013
DOI: 10.1186/1756-3305-6-130
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of long-lasting insecticidal nets against pyrethroid-resistant populations of Anopheles gambiae s.s. from different malaria transmission zones in Uganda

Abstract: BackgroundThere are major concerns over sustaining the efficacy of current malaria vector control interventions given the rapid spread of resistance, particularly to pyrethroids. This study assessed the bioefficacy of five WHO-recommended long-lasting insecticidal nets (LLINs) against pyrethroid-resistant Anopheles gambiae field populations from Uganda.MethodsAdult An. gambiae from Lira, Tororo, Wakiso and Kanungu districts were exposed to permethrin (0.75%) or deltamethrin (0.05%) in standard WHO susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 33 publications
7
72
0
Order By: Relevance
“…These findings indicate that PermaNet® 2.0 and improved PermaNet® 3.0 (with PBO) are advanced tools for protection against resistant populations of An. gambiae mosquitoes [8, 17, 37]. This efficacy has also been observed in Ethiopia [9] and Cote d’Ivoire [18].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings indicate that PermaNet® 2.0 and improved PermaNet® 3.0 (with PBO) are advanced tools for protection against resistant populations of An. gambiae mosquitoes [8, 17, 37]. This efficacy has also been observed in Ethiopia [9] and Cote d’Ivoire [18].…”
Section: Discussionmentioning
confidence: 70%
“…gambiae ) across Africa could represent a threat to the tools currently used for vector control [814]. Resistance to every currently used insecticide has been found and many factors are believed to increase vector resistance including the extensive use and misuse of the same classes of insecticides in agriculture and public health sectors [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there is limited evidence that pyrethroid resistance is undermining the effectiveness of LLINs [47]. Laboratory experiments in which wild, resistant Anopheles strains are directly exposed to net samples have indicated reduced efficacy of LLINs against resistant strains [4850], while experimental hut studies and field studies have demonstrated that resistant mosquitoes are more likely to enter LLINs, feed upon the occupants and survive [15, 16]. However, to date there is insufficient evidence on the epidemiological significance of the observed pyrethroid resistance on LLINs in the community.…”
Section: Discussionmentioning
confidence: 99%
“…To date long lasting insecticidal nets (LLINs) and indoor residual spray (IRS) have remained at the core of malaria intervention in endemic areas. The LLINs provide both a physical barrier to mosquitoes and insecticidal effects [13,14]. The IRS has an effect on the mortality of malaria vectors when they rest on treated surfaces and are therefore susceptible to the insecticides applied on them.…”
Section: Introductionmentioning
confidence: 99%